2008
DOI: 10.1101/gr.083931.108
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific gene expression patterns in primary leukemic cells reveal regulation of gene expression by CpG site methylation

Abstract: To identify genes that are regulated by cis-acting functional elements in acute lymphoblastic leukemia (ALL) we determined the allele-specific expression (ASE) levels of 2529 genes by genotyping a genome-wide panel of single nucleotide polymorphisms in RNA and DNA from bone marrow and blood samples of 197 children with ALL. Using a reproducible, quantitative genotyping method and stringent criteria for scoring ASE, we found that 16% of the analyzed genes display ASE in multiple ALL cell samples. For most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 44 publications
4
64
0
3
Order By: Relevance
“…This result is also supported by our recently published findings indicating that hypermethylation of the downstream ABCB1 downstream promoter upon acquisition of docetaxel resistance in MCF-7 cells results in exclusive usage of the upstream promoter for ABCB1 transcription. 16 There have also been previous reports of allele-specific gene expression linked to allele-specific methylation of genes, 29 although this has not been reported for the ABCB1 gene. However, one study has determined that ABCB1 expression can occur from one allele while the other is transcriptionally silent in drug-resistant cell lines and relapsed lymphoma samples, 30 further supporting differential regulation of ABCB1 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…This result is also supported by our recently published findings indicating that hypermethylation of the downstream ABCB1 downstream promoter upon acquisition of docetaxel resistance in MCF-7 cells results in exclusive usage of the upstream promoter for ABCB1 transcription. 16 There have also been previous reports of allele-specific gene expression linked to allele-specific methylation of genes, 29 although this has not been reported for the ABCB1 gene. However, one study has determined that ABCB1 expression can occur from one allele while the other is transcriptionally silent in drug-resistant cell lines and relapsed lymphoma samples, 30 further supporting differential regulation of ABCB1 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are critical in certain examples of gene regulation, including dosage compensation in mammals and immunoglobin diversity in the immune system. Indeed, more recent surveys have indicated that complete or partial differential allelic expression affects up to 20% of genes in mammals (Serre et al 2008;Milani et al 2009). Differential allelic expression also occurs in many diverse organisms, suggesting that it is a widespread feature of gene regulation.…”
mentioning
confidence: 99%
“…Большинство генов, при экс-прессии которых выявлялся аллельный дисбаланс, кодировали белки, обеспечивающие процессирование и представление (презентацию) антигенов, процессы межклеточной адгезии и контакты с внеклеточным матриксом (например, синдекан-2, гиперэкспрессию которого наблюдают в нескольких типах опухолей), а также матриксные белки. Высокая корреляция ал-лельного дисбаланса экспрессии генов и метилирова-ния CpG-островков в их промоторах или первых интро-нах указывает на способность полиморфизмов влиять на аллель-специфическое метилирование [16].…”
Section: обзорные статьиunclassified
“…Это позволяет предположить, что в качестве их причин выступают одни и те же цис-регуляторные варианты. Кроме того, показано, что 38-88 % сайтов аллель-специфического метилирова-ния зависят от наличия в CpG-островках полиморфиз-мов, нарушающих метилирование этих участков [16,17]. Поскольку мутации в CpG-островках являются доста-точно частым событием [17], аллель-специфическое метилирование может определять индивидуальные раз-личия в паттернах аллель-специфической экспрессии.…”
unclassified